Epidemiology of Invasive Fungal Infections at Two Tertiary Care Neonatal Intensive Care Units Over a 12-Year Period (2000-2011). (22nd March 2017) - Agarwal, Roshani R.; Agarwal, Rajkumar L.; Chen, Xinguang; Lua, Jorge L.; Ang, Jocelyn Y.
We conducted a retrospective review of 168 patients with invasive fungal infections from January 2000 to December 2011 in 2 neonatal intensive care units. Patients with Candida bloodstream infection (BSI, n = 152) were further analyzed. C albicans was the most common species overall (47%); however, there was an increase in non– albicans sp from 2006 to 2011. Candida BSI clearance rates were lower in extremely low birth weight infants (77% vs 93%, P = .01) and in patients with C albicans infections (77% vs 91%, P = .01). Clearance rates improved from 2000 to 2005 (70% - 90%) to 2006 to 2011 (86% -100%). Combination antifungal use increased during the later years (73% vs 49%, P < .05) and in patients with end-organ dissemination (83% vs 54%, P < .05). We concluded that extremely low birth weight infants and C albicans infection are factors associated with nonclearance of Candida BSI. Successful clearance of Candida BSI improved in 2006 to 2011, perhaps due to increase in non– albicans species and the use of combination antifungals.